ANALISIS KEMAMPUAN WEBRATIO UNTUK PENGEMBANGAN APLIKASI WEB MENGGUNAKAN INTERACTION FLOW MODELING LANGUAGE (IFML) - Min, Joe Lian (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
The model-driven development (MDD) method is a method that can accelerate the application development process. With this method, the model can be immediately transformed into an executable application. Model-driven architecture is one kind of MDD approaches. MDA has a standard modeling language that is used to facilitate the transformation process. One of the modeling languages in MDA is Interaction Flow Management Language (IFML). IFML models an application based on the interaction flow and interface of the application. This paper explains the capabilities of WebRatio in developing Web applications and their effectiveness. The effectiveness is calculated from the effort required for the development. On the other side, the effort is calculated from the line of code (LOC) generated from the model. The experiment's case study is aÂ  simple web-shop application, with some functional and non-functional requirements. The measurement results show that to develop a web-shop, the effort required is quite efficient, only 13% of the total application. However, another study still needs to be done because many variables affect the productivity of application development.